Performance of calves fed cheese whey associated with colostrum - Lima, Renata Nayhara de; Lima, Patrícia de Oliveira; Aroeira, Luiz Januário Magalhães; Miranda, Maria Vivianne Freitas Gomes de; Lopes, Kátia Tatiana de Lima; Diógenes, Géssica Vitalino; Pereira, Maria Izabel Batista; Souza, Isis Thamara do Nascimento; Rossato, Cristiano Herculano (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the performance of crossbred calves fed cheese whey, in association with colostrum. Twenty‑four Holstein x Zebu calves, distributed in a completely randomized block design, with three treatments and eight replicates, were used. The treatments consisted of: whole milk; 50% whole milk + 50% cheese whey; and 30% colostrum + 70% cheese whey. The development of calves was evaluated until 60 days of age by weekly weighing and body measurements. To estimate consumption, daily measurements of solid diet consumption were done by the supply/spare method. Economic performance was evaluated by calculating indicators of costs and revenues, and measurements of economic outcomes. There was no influence of liquid diet on dry matter intake and on average body measurements of calves. Significant differences were found in animal weight gain in the second and in the fourth weeks of life. The diet containing colostrum showed the highest additional profit when compared to the control treatment. The association of cheese whey and colostrum is the most economically advantageous option in the liquid diet of crossbred calves, since the substitution of 100% of the milk by these byproducts did not harm the performance of animals.